Bioanalytical methods for the metalloproteomics study of bovine longissimus thoracis muscle tissue with different grades of meat tenderness in the Nellore breed (Bos indicus) - Baldassini, Welder Angelo [UNESP]; Braga, Camila Pereira [UNESP]; Loyola Chardulo, Luis Artur [UNESP]; Ii Vasconcelos Silva, Josineudson Augusto [UNESP]; Malheiros, Jessica Moraes [UNESP]; Albuquerque, Lucia Galvao de [UNESP]; Fernandes, Talita Tanaka [UNESP]; Padilha, Pedro de Magalhaes [UNESP] (Elsevier B.V., 2015)
The work describes a metalloproteomics study of bovine muscle tissue with different grades of meat tenderness from animals of the Nellore breed (Bos indicus) based on protein separation by two-dimensional gel electrophoresis, the identification of calcium ions in protein spots by X-ray fluorescence (SR-XRF) and the characterisation of proteins by electrospray ionisation mass spectrometry. Forty (40) specimens were selected and divided into two experimental groups: animals with tough meat (TO) and animals with tender meat (TE). A third group (P) of Piedmontese breed animals (Bos taurus) was included to serve as a comparative model for the level of meat tenderness. The procedures were efficient and preserved the metal protein structure, enabling calcium detection in protein spots by SR-XRF at a given molecular weight range of 14-97 kDa. Two proteins (pyruvate kinase and albumin) were inferred to be related to the phenotypical differences in animals from the different groups. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 2D-PAGE; Beef cattle; Calcium; Mass spectrometry; Zebu genotype